Reduplication as a compounding process: the case of [VV] converbs in Turkish - Yıldız, Esra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
This study investigates the nature of Turkish [V(erb) V(erb)] constructions that are converbs (henceforth, [VV] converbs). Turkish [VV] converbs can bear various converbial markers and the ones focused in this study are constructed either with the imperative marker, the optative marker or the conjunctive marker. This study argues that [VV] converbs are in fact compounds generated by the process of reduplication. To investigate their reduplicative status, Morphological Doubling Theory (MDT) of Inkelas and Zoll (2000, 2005) and Inkelas (2005, 2008, 2014) is adapted in the study. MDT claims that the constituents of a reduplicative construction must have identical morphosyntactic features and they must be semantically-related. This study also shows that [VV] converbs are not ordinary reduplications because these structures have compound-like behaviors (e.g. inseparability). This study further argues that being both reduplications and compounds renders [VV] converbs co-compounds (i.e. a sub-type of compounds). The model of Wälchli (2005) is adopted to explain their co-compound status. Wälchli (2005) claims that natural coordination (i.e coordination of items which are expected to co-occur) and double-headedness mark cocompounds as a distinct class among compounds. Moreover, the present study aims to investigate whether [VV] converbs in Turkish are constructed in phonology, morphology or syntax. After considering all three, this study proposes that only syntax appears to account for all of [VV] converbs properties. All these theoretical considerations are made on data collected from dictionaries, the TS corpus (http://tscorpus.com/tr) and various blogs on the internet. This data shows that [VV] converbs are highly frequent and productive.
Keywords: Turkish language -- Verb.